Pendidikan Karakter Di Madrasah - Zainal Arifin (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The character has suddenly become a warm discourse in the Indonesian education world. Although the idea of character happenings is an old idea, as old as education history, but the emergence of the idea of "character education" interfered with our nation, especially those who are engulfed in Indonesia. Problems that occur such as violence, corruption, manipulation, the practices of lies in the educational world ranging from cheating in the exam to plagiarism, lack of precision among the leaders of the nation, and so on, in fact concerns about character problems. Although it is too late in implementing character education in the school, "But late than never", there are still many generations of students who are sitting in the schools and need character education in the future to be a person who is not only intelligent Intellect but also has a character. The education is also to build ethics and manners in life. The character restrictions are in two areas. It is believed to exist as human-nature, while on the other hand it is believed to be "formed" through education, one of them through character education in the school. The implementation of education character in the alternative is presented by bidding with the Formula 4 M (knowing, loving, wanting and working, also with habituation method. In addition through methods of teaching, transparency, determining priority and practice priorities.